De indio a peruano: El indígena andino entre las cortes de Cádiz y el primer Congreso Constituyente del Perú - Saavedra Inaraja, María (2009)
The birth of the Republic of Peru and its political construction went through the difficult process of incorporating population groups with very different characteristics into a liberal State, among which is the great mass formed by the indigenous population. The treatment that the indigenous issue had in the Cortes of Cádiz by the Peruvian deputies, and what that treatment was in the sessions of the first Constituent Congress of Peru, a decade later, is studied. In both constituent processes, elements of legislative effectiveness are reflected along with other elements that are the expression of pure rhetorical activity.